Triggers of traveler willingness to use and recommend eco-friendly airplanes - Han, Heesup; Lee, Myong Jae; Chua, Bee Lia; Kim, Wan Soo (Elsevier, 2019)
With the limited current research about eco-friendly electric airplanes, this research was designed to investigate the formation of customers' pro-environmental intentions to use and recommend electric airplanes. A quantitative approach with structural equation modeling was used. Our empirical findings revealed that eco-concerns, anticipated affects, social norm, and sense of obligation to take pro-environmental actions played a vital role in generating intentions, and the proposed conceptual framework comprising these variables satisfactorily accounted for the total variance in intentions. Positive anticipated emotions and sense of obligation to take pro-environmental actions acted as mediators. Moral obligation and social norm were of greatest importance in determining purchase and recommendation intentions, respectively. Moreover, the test for metric invariance revealed that the role of moral obligation in determining recommendation intention was maximized when green product involvement level was high. Our results offered a sufficient understanding of customer decision-making process for eco-friendly electric airplanes.